Beginning JSP, JSF and Tomcat Java Web Development - Zambon, Giulio; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
Start building Java–based web applications now, even if you’re a complete newcomer to Java. Comprehensive and example–driven, Beginning JSP, JSF, and Tomcat: Java Web Development, Second Edition is all you need to develop dynamic Java-based web applications using JSP, connect to databases with JSF, and put them into action using the world’s most popular open source Java web server, Apache Tomcat. A comprehensive introduction to JavaServer Pages (JSP), JavaServer Faces (JSF), and the Apache Tomcat web application server Key concepts made easy to grasp by numerous working examples and a walkthrough of the development of a complete e-commerce project Written for professionals by a practicing Java web application professional and expert.
Keywords: Java (Computer program language).; Software engineering; Java; Software Engineering/Programming and Operating Systems